Comparative analysis of the genomes of Stylophora pistillata and Acropora digitifera provides evidence for extensive differences between species of corals - Voolstra, Christian R.; Li, Yong; Liew, Yi Jin; Baumgarten, Sebastian; Zoccola, Didier; Flot, Jean-François; Tambutté, Sylvie; Allemand, Denis; Aranda, Manuel (Scientific reports, 2017)
Stony corals form the foundation of coral reef ecosystems. Their phylogeny is characterized by a deep evolutionary divergence that separates corals into a robust and complex clade dating back to at least 245 mya. However, the genomic consequences and clade-specific evolution remain unexplored. In this study we have produced the genome of a robust coral, Stylophora pistillata , and compared it to the available genome of a complex coral, Acropora digitifera . We conducted a fine-scale gene-based analysis focusing on ortholog groups. Among the core set of conserved proteins, we found an emphasis on processes related to the cnidarian-dinoflagellate symbiosis. Genes associated with the algal symbiosis were also independently expanded in both species, but both corals diverged on the identity of ortholog groups expanded, and we found uneven expansions in genes associated with innate immunity and stress response. Our analyses demonstrate that coral genomes can be surprisingly disparate. Future analyses incorporating more genomic data should be able to determine whether the patterns elucidated here are not only characteristic of the differences between S. pistillata and A. digitifera but also representative of corals from the robust and complex clade at large.